Lactobacillus acidophilus Supplementation Exerts a Synergistic Effect on Tacrolimus Efficacy by Modulating Th17/Treg Balance in Lupus-Prone Mice via the SIGNR3 Pathway - Kim, Da Som; Park, Youngjae; Choi, Jeong-Won; Park, Sung-Hwan; Cho, Mi-La; Kwok, Seung-Ki (Frontiers in Immunology, 2021)
Objective: Tacrolimus (Tac) is an immunosuppressant used in the treatment of systemic lupus erythematosus (SLE); however, it induces T cell subset imbalances by reducing regulatory T (Treg) cells. Lactobacillus acidophilus (LA) is reported to have therapeutic efficacy in immune-mediated diseases via T cell regulation. Methods: This study investigated whether a combination therapy of LA and Tac improves the therapeutic efficacy of Tac by modulating T cell subset populations in an animal model of SLE. Eight-week-old MRL/lpr mice were orally administered with 5 mg/kg of Tac and/or 50 mg/kg of LA daily for 8 weeks. Caecal microbiota compositions, serum autoantibodies levels, the degree of proteinuria, histological changes in the kidney, and populations of various T cell subsets in the spleen were analyzed. Results: Mice presented with significant gut dysbiosis, which were subsequently recovered by the combination treatment of Tac and LA. Double negative T cells in the peripheral blood and spleens of MRL/lpr mice were significantly decreased by the combination therapy. The combination treatment reduced serum levels of anti-dsDNA antibodies and Immunoglobulin G2a, and renal pathology scores were also markedly alleviated. The combination therapy induced Treg cells and decreased T helper 17 (Th17) cells both in vitro and in vivo. In vitro treatment with LA induced the production of indoleamine-2,3-dioxygenase, programmed death-ligand 1, and inerleukin-10 via the specific intracellular adhesion molecule-3 grabbing non-integrin homolog-related 3 receptor signals. Conclusion: The present findings indicate that LA augments the therapeutic effect of Tac and modulates Th17/Treg balance in a murine model of SLE.